Impact of Character Education on Student Social Behavior - Cahyani, Vika Puji; Ahmad, Fandi (Jurnal Pendidikan Karakter JAWARA (Jujur, Adil, Wibawa, Amanah, Religius, Akuntabel), 2024)
Character education not only focuses on instilling values, but also aims to create an educational environment where individuals can exercise their freedom responsibly, laying the foundation for moral maturity. Although there is evidence that character education can improve students' social behavior, it is still unclear how character education affects relationships between students. Thus, this study aims to examine the impact of character education on students' social behavior at school. This research is a qualitative research with Literature review approach. In literature review, researchers collect, evaluate, and present information from various literature sources such as scientific journals, books, and articles to understand the development of existing knowledge, identify knowledge gaps, and develop a strong theoretical foundation for the research to be conducted. The findings of this study are that character education serves as a foundational element in shaping student relationships within the school community, fostering values, attitudes and behaviors that promote a positive and supportive learning environment.  The importance of character education in shaping students' character, values and social competence ultimately contributes to their overall development and well-being. Character education has a significant role in reducing negative behaviors such as bullying in schools. Through learning moral values, developing empathy and reinforcing positive attitudes, character education can help create a safe, inclusive and supportive school environment for all students.